Relationship between clinical, laboratory, and radiological parameters with polymerase chain reaction positivity sputum in adult HIV patients with suspicion of pneumocystis jirovecii pneumonia - Atmaja, Kadek Surya; Somia, I Ketut Agus; Krisdanti, I Desak Putu Agung; Candrawati, Ni Wayan; Kusumawardani, Ida Ayu Jasminarti Dwi; Arisanti, Ni Luh Putu Eka (Edelweiss Applied Science and Technology, 2025)
Pneumocystis jirovecii pneumonia (PCP) is a fungal infection of the lungs caused by P. jirovecii, usually affecting patients with Human Immunodeficiency Virus (HIV). The polymerase chain reaction (PCR) test is used in the diagnosis of PCP and has good sensitivity, but it is not available in all healthcare facilities. Clinical, laboratory, and radiological parameters can serve as alternatives to support the diagnosis of PCP in HIV patients. This study is an analytical observational study with a cross-sectional design. The assessment of clinical, laboratory, and radiological parameters of PCP patients was conducted from June to December 2024. Variables were compared using the Independent T-test if normally distributed or the Mann-Whitney test if not normally distributed. Nominal variables were compared using the Chi-square test. Multivariate analysis employed logistic regression analysis. A total of 80 patients participated in the study. From the multivariate analysis, clinical parameters such as low-grade fever (PR 23.9; 95% CI 4.086–141.01; p < 0.001), non-productive cough (PR 7.108; 95% CI 1.25–40.1; p = 0.027), and oral candidiasis (PR 8.81; 95% CI 1.62–47.8; p = 0.012) were significant. Laboratory parameters such as lymphocyte count ≤1.2×10³/µL (PR 19.4; 95% CI 2.5–149.3; p = 0.004), albumin ≤ 3.1 g/dL (PR 5.59; 95% CI 1.062–29.4; p = 0.042), and CD4 count ≤ 200 cells/µL (PR 14.3; 95% CI 2.06–99.69; p = 0.007) were also significant. Typical radiological parameters (PR 20.6; 95% CI 2.9–144.2; p = 0.02) and atypical radiological parameters (PR 5.43; 95% CI 1.47–20.05; p = 0.02) showed a significant relationship with sputum PCR positivity for PCP in HIV patients. Low-grade fever, non-productive cough, oral candidiasis, lymphocyte count ≤1.2×10³/µL, albumin ≤ 3.1 g/dL, CD4 count ≤ 200 cells/µL, and typical and atypical chest X-ray images are associated with sputum PCR positivity in HIV patients suspected of having PCP.